Nanocluster Optical Resonance Devices for Molecular Structure Transduction - Haglmuller, Jakob; Matyushin, Viacheslav; Rauter, Harald; Mayer, Christian; Winkler, Heinz; Bauer, Georg; Schalkhammer, Thomas (Current Nanoscience, 2005)
Resonant enhancement of metal cluster light absorption (REA) is an effective means to set up novel nanooptical devices. The boosting of optical absorbance is achieved by a resonant four component system. A metal mirror, a polymer or glass type nano-distance layer, a reactive bio-molecule layer and a sub-monolayer of bound metal nanoclusters are employed. Decisive for these types of devices and sensors is the precise nanometric assembly that couples the local field surrounding a cluster with its mirror-dipole. Metal clusters (synthesized by chemical reduction or deposited by vacuum coating techniques), metal-dielectric shell clusters (synthesized by multiple shell deposition processes) as well as high quality tuning of the distance layer enabled us to precisely shift the readout of the device to any frequency in the visible and near IR range. Sensors show one to three narrow or broad-band reflection minima in the visible and/or infra part of the spectrum. These are tuned by adjustment of the geometric parameters of the setup (Fig. (1)). Devices are used for detection of biorecognitive binding and monitoring structural changes of nucleic acids, proteins or analyte-recognitive polymers. The chip responds to the presence or absence of an analyte by a conformational change of the bio/polymer-transducer, thereby changing the cluster-mirror distance (or cluster distribution) and thus the optical absorbance and color of the chip. Disposable single step protein chips, DNA assays, RNA-conformation chips and polymer-artificial noses as well as complex arrays make use of the novel conformation-color transducer.
Keywords: metal nano-clusters